Tahlil Kematian Sebagai Tradisi Dalam Ajaran Islam Perspektif M. Quraish Shihab - Nur Halimatus; Ummi Aida; Febri Ana Nurfanisa (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
Tradition is one way to perpetuate Islamic teachings, in Indonesia with its many tribes, races and also cultures and even religions, of course it is clear that traditions are born in each region, such as the tahlil tradition of death, which almost all Muslims in Indonesia carry out this tradition, regardless of the affiliation with  death or not, recently it has been debated regarding the tradition of tahlil death is not an Islamic teaching by reflecting that it was not carried out by the prophet and the sequences that were burdensome to the executors, so it is important to disclose to the public regarding the design of the tradition carried out, as well as its conformity with Islamic teachings.  This study uses a descriptive qualitative method that guides research to explore broadly, using two data sources.  Primary and secondary, the primary data source is the leader of the implementation of the death tahlil tradition, the secondary data source comes from the executors and the participating community, while the method of data collection uses observation and interviews by reducing data as concentration, then presentation, and finally drawing conclusions.  With the result that the tahlil tradition of death has been carried out for a long time and is based on the request of the host, based on beliefs that are oriented towards the Al-Quran and Sunnah, with the corridors of Islamic teachings, because it has the scope of characteristics described by M Quraish Shihab;  Rabbaniyah, Insaniyah, Alamiyah, Wasathiyah, Waqi'iyah, Al-Wudhuh, 'Adam Al-Haraj.